Green Technological Investments and Their Impacts on Ecological Innovation in Entrepreneurship - Mirmohamma Seyednouri; Ali Farzpourmachiani; Seyedehmona Modaresrad; Mercede Ostadsandiani; Saeid Basiri; Salar Basiri; Mehdi Farzpourmachiani (Journal of Biotropical Research and Nature Technology, 2026)
Green technology investments-public and private capital invested in renewable energy, resource efficiency, circular economy solutions, and other low-carbon technologies-are widely argued to catalyze ecological (eco-) innovation among entrepreneurial firms. This review synthesizes theoretical frameworks and empirical evidence on how green investments influence ecological innovation in entrepreneurship. We organize the literature around four mechanisms-finance and risk reduction, knowledge/technology transfer, market signaling and demand creation, and institutional/policy levers-and summarize sectoral heterogeneity, enabling conditions, barriers, and policy implications. Two short summary tables highlight empirical studies and policy instruments; a conceptual figure illustrates the mechanisms linking green capital to eco-innovation. We conclude with practical recommendations for entrepreneurs, investors, and policymakers and point to promising directions for future research.